Phylogeny and revision of a colorful Neotropical genus of rove beetles: Xenopygus Bernhauer (Coleoptera: Staphylinidae) - Caron, Edilson; Castro, Jessica C. De; Silva, Maycon R. Da; Ribeiro-Costa, Cibele S. (Zootaxa, 2016)
Xenopygus Bernhauer is one of the most colorful staphylinid beetles and widespread in the Neotropical region. The aim of this study was to test the monophyly of Xenopygus based on adult morphology and to review the current species. Cladistic analysis was performed with six ingroup species, including two new species. Xenopygus is a monophyletic group supported by: antennomere V as wide as long to slightly wider, antennomere VII two times wider than long and superior line of pronotal hypomere developed, continuous on the anterior angle of pronotum. Xenopygus is composed of six species, four previously described and two new species, with the following topology: ((X. analis+(X. bicolor+X. confusus))+(X. cordovensis+(X. sancticamillus, sp. nov.+ X. petilicolis, sp. nov.))). Xenopygus is the sister group to a clade formed by species of Dysanellus and Xanthopygus, corroborating previous phylogenetic studies. The genus, and all its species were redescribed, an identification key was produced and illustration diagnostic plates and distribution maps were also provided.